GDGTs as indicators for organic-matter sources in a small subtropical river-estuary system. (March 2021) - Cheng, Zhangyu; Yu, Fengling; Ruan, Xiaoyan; Cheng, Peng; Chen, Nengwang; Tao, Shuqin; Zong, Yongqiang; Yang, Huan; Huang, Zhaoquan
Highlights: GDGTs could indicate organic-matter (OM) sources in a small river-estuary system. The GDGT-0/cren and bGDGTs indicated anthropogenic-induced water eutrophication. The BIT estimated well the soil vs marine OM inputs in the estuary. Estuarine OM distribution was influenced by OM sources and preservation processes. Abstract: Recently, glycerol dialkyl glycerol tetraethers (GDGTs) have been successfully used to identify different sources for organic-matter in the offshore and open ocean areas, while their applicability in the coastal areas remains unclear. This study was carried out to investigate the behavior of GDGTs and their applicability as indicators for organic-matter sources in a small subtropical river-estuary system, the Jiulong River-Estuary system (JRES), southeastern China. In 2018, three groups of samples including riverbank soils, riverbed surface sediments, and estuarine surface sediments were collected and analyzed. The results supported three main findings: 1) The abundances of GDGTs and crenarchaeol, and the ratios of iGDGTs/bGDGTs, GDGT-0/crenarchaeol (GDGT-0/cren), crenarchaeol isomer / (crenarchaeol + crenarchaeol isomer) and the IIIa/IIa, were good indicators for organic-matter sources; 2) At the middle and lower reaches of West River, the abnormally high values of GDGT-0/cren ratio and bGDGT abundance might indicate anthropogenic-induced water eutrophication; and 3) The branched and isoprenoid tetraether index (BIT) was especially sensitive in indicating of the soil- vs marine-organic matter contribution to the total organic matter of estuarine sediments. The high BIT values at the estuary turbidity maximum zone (TMZ) and the mid estuary suggested that TMZ filtering effect, preservation conditions and extra sources of soils have impacted the organic-matter distribution. Understanding the behavior and application of GDGTs in such a system helps to improve research on organic carbon cycling in the coastal system.